Hubungan Antara Komunikasi Dosen dengan Mahasiswa Unisba dalam Pemenuhan Kebutuhan Belajar di Masa Pandemi - Mochamad Isya Anshori (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Currently the world is being shocked by the outbreak of covid 19, then the Indonesian government imposed an emergency status that obliges him to work from the household of the Unisba community. Their faces become communicating as well as students communicating with lecturers. The research was conducted at the Islamic University of Bandung on Jl Tamansari No.1 Bandung 40116. The model in this study is the SMCR of David K ​​Berlo (Source, Message, Channel, Receiver) namely